Effect of Atorvastatin Treatment on Serum Paraoxonase-1 Level in Hyperlipidemic Patients - Özkan, Yusuf; Koca, Süleyman Serdar; Gürsu, Ferit; Sonkaya, Ertuğrul; Poyrazoğlu, Orhan Kürşad; Dönder, Emir (Fırat University, 2004)
Introduction: Atherosclerosis-based diseases like coronary artery disease, myocardial infarction and stroke are leading causes of morbidity and mortality. Hyperlipidemia is among the major risk factors of atherosclerotic diseases and results in accelerated atherosclerosis. Paraoxonase-1 (PON1), an antioxidant enzyme, is reported to have a protective role in the atherosclerotic process, by contributing to the protective effect of HDL and preventing the oxidation of LDL cholesterol. Atorvastatin, a member of the class of statins, which are potent lipid-reducers, is widely used in hyperlipidemia. It was shown that PON1 level decreased in dyslipidemia. The studies on the effects of various lipid-reducing agents on PON 1 levels produced conflicting results. In the present study we aimed to examine the effect of atorvastatin treatment on serum PON1 level. Material and Methods: Sixty hyperlipidemic patients were treated with 10mg/day atorvastatin for 12 weeks. Serum lipids and PON1 levels were examined at the beginning of the study, in the first and third months and then, compared. Results: Twelve-week atorvastatin treatment brought about favorable changes in lipid profile, in consistency with the literature. Basal PON1 value was 186.94±40.13 (unit/L), whereas PON1 values were 205.60±44.79 (unit/L) in the first month and 226.00±40.15 (unit/L) in the third month. Serum PON1 value was observed to have statistically significantly increased in the third month, when compared to basal values. Conclusion: Atorvastatin treatment increases levels of PON1, which is reported to assume a protective role in atherosclerosis, in addition to producing positive changes in the lipid profile. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Giriş: Koroner arter hastalığı, miyokard infarktüsü, inme gibi ateroskleroz temelli hastalıklar önde gelen morbidite ve mortalite sebepleridir. Hiperlipidemi aterosklerotik hastalıkların major risk faktörlerindendir ve hızlanmış ateroskleroz ile sonuçlanmaktadır. Antioksidan bir enzim olan Paraoksonaz-1'in (PON1), HDL'nin koruyucu etkisine katkıda bulunarak ve LDL kolesterolün oksidasyonunu önleyerek, aterosklerotik süreçte koruyucu bir role sahip olduğu bildirilmektedir. Potent lipid düşürücülerden statinlerin bir üyesi olan atorvastatin hiperlipidemide yaygın olarak kullanılmaktadır. PON1 düzeyinin, dislipidemide azaldığı ortaya konmuş ve çeşitli lipid düşürücü ajanların PON1 düzeylerine etkileri araştırılmıştır. Bu araştırmalarda çelişkili sonuçlar ortaya konmuştur. Bu çalışmada atorvastatin tedavisinin serum PON1 düzeyine etkisini araştırmayı amaçladık. Gereç ve Yöntem: 60 hiperlipidemik hasta 10 mg/gün atorvastatin ile 12 hafta süreyle tedavi edildi. Tedavinin başlangıcında, birinci ve üçüncü aylarında serum lipitleri ve PON1 düzeylerine bakıldı ve karşılaştırıldı. Bulgular: 12 haftalık atorvastatin tedavisi; lipid profilinde literatüre uygun olarak olumlu değişikliklere yol açtı. Ayrıca PON1 bazal değeri 186.94±40.13 (ünite/L) iken birinci ayda 205.60±44.79 (ünite/L) ve üçüncü ayda 226.00±40.15 (ünite/L) olarak saptandı. Serum PON1 düzeyinin üçüncü ayda bazal değerlere göre istatistiksel olarak anlamlı derecede arttığı gözlendi. Sonuç: Atorvastatin tedavisi lipit profilinde olumlu değişikliklere ilaveten aterosklerozda protektif rol üstlendiği bildirilen PON1 düzeylerinde artışa yol açmaktadır. ©2004, Fırat Üniversitesi, Tıp Fakültesi
HİPERLİPİDEMİK HASTALARDA ATORVASTATİN TEDAVİSİNİN SERUM PARAOKSONAZ-1 DÜZEYİNE ETKİSİ